S50 Camphor score: sustained improvement in patient reported outcomes following pulmonary endarterectomy in chronic thromboembolic pulmonary hypertension. (15th November 2017) - Newnham, M; Bunclark, K; Abraham, N; Almeida, L Amaral; Cannon, J; Clare, S; Doughty, N; Dunning, J; Ng, C; Ponnaberanam, A; Scholtes, S; Sheares, K; et al.
Abstract : Introduction: The CAMPHOR (Cambridge Pulmonary Hypertension Outcome Review) score is an internationally validated patient reported outcome (PRO) measure for pulmonary hypertension, including chronic thromboembolic pulmonary hypertension (CTEPH). It assesses 3 areas: activity (score 0–30), symptoms (0–25) and quality of life (QoL) (0–25); with a higher score indicating a worse PRO. CTEPH frequently causes debilitating symptoms and functional impairment, which can be improved in selected patients with pulmonary endarterectomy (PEA). However, a subset will have residual pulmonary hypertension. We aim to assess PROs in patients with CTEPH undergoing PEA. Methods: Consecutive CTEPH patients undergoing PEA from June 2006 to August 2016 at the UK National PEA centre, were included in this retrospective analysis. Patients are reviewed after PEA every 6–12 months for at least 5 years. CAMPHOR scores were recorded prospectively when patients attended hospital assessment and at each follow-up, ensuring high capture. Results: 1151 patients underwent PEA during the study period. Of those, 937 (81%) had a CAMPHOR score recorded at baseline (pre-PEA) and 816 (77% of 1059 alive) at follow-up within a year of PEA (post-PEA). We confirmed significant improvements in 6 min walk distance and haemodynamics post-PEA (pre/post-PEA median ±IQR: 6 mwd 300±199 Metres/360±165; mPAP 45±15/25±13 mmHg; PVR 669±478/246±214 dynes.s.cm -5 ; CI 2.2±0.8/2.3±0.7 L/min/m 2 ). The difference in median CAMPHOR scores pre- and post-PEA improved by 6, 7 and 9 points for activity, QoL and symptoms respectively. The median difference for individuals having consecutive paired pre- and post-PEA scores also improved (median ±IQR: activity 4±7; QoL 4±8; symptoms 7±8). Patients were dichotomised into those with significant residual pulmonary hypertension (previously reported risk threshold of ≥30 mmHg, n=302) and those without (n=569). The improvement in CAMPHOR score was greater and more sustained in those without residual pulmonary hypertension (fsigure 1). Conclusion: PROs relating to activity, QoL and symptoms improve after PEA in CTEPH when evaluated by CAMPHOR score. The improvement is sustained up to 5 years in those without residual pulmonary hypertension. Ongoing work will examine the utility of PROs in addition to traditional clinical outcome measures. Acknowledgements: National Pulmonary Hypertension Centres UK and Ireland for referring patients considered for PEA.